Pelatihan Literasi Keuangan Melalui Metode Story Telling Pada Anak Usia Dini - Astuti, Fitria Yuni; Abdul Khafid; Umi Hani; Gilang Kharisma Putra; Nurifa Laksmitasari Azizah (Jurnal AbdiMas Ekonomi Terapan, 2024)
In this era of globalization, consumer culture has become an undeniable part of the culture in our environment, so it is not easy to differentiate between the most important needs and those needs that do not have to be fulfilled or are called desires. Teaching children from an early age about financial literacy is our shared task/homework. The aim of this community service is to train children to be able to manage their finances well, wisely and on target by saving. The object of this training is students studying at TPQ.Darussalam, with delivery using the story telling method, it is hoped that the participants will be able to absorb material regarding financial literacy which is packaged with a more interesting story so that it makes the participants happy and enthusiastic.